Willingness and ability to pay for unexpected dental expenses by Finnish adults - Widström Eeva; Seppälä Timo (BMC, 2012)
Abstract Background Since 2002, adults have been able to choose oral health care services in the public sector or in the private sector in Finland. Though various subsidies for care exist in both sectors, the Public Dental Service (PDS) is a cheaper option for the patient but, on the other hand, there are no waiting lists for private care. The aim of this study was to assess middle-aged adults' use of dental services, willingness to pay (WTP) and ability to pay (ATP) for unexpected, urgent dental treatment. Methods Postal questionnaires on use of dental services were sent to a random sample of 1500 47-59 year old adults living in three large municipalities in the Helsinki region. The initial response rate was 65.8%. Two hypothetical scenarios were presented: "What would be the highest price you would be prepared to pay to have a lost filling replaced immediately, or, at the latest, the day after losing the filling?" and " How much could you pay for unexpected dental expenses at two weeks notice, if you suddenly needed more comprehensive treatment?" Logistic regression analysis was used to analyse factors related to WTP and ATP. Results Most respondents (89.6%) had visited a dentist recently and a majority (76.1%) had used private services. For immediate replacement of a lost filling, almost all respondents (93.2%) were willing to pay the lower price charged in the PDS and 46.2% were willing to pay the private fee. High income and no subjective need for dental treatment were positively associated with the probability of paying a higher price. Most respondents (93.0%) were able to pay a low fee, EUR 50 and almost half (41.6%) at least EUR 300 for unexpected treatment at short notice. High income and male sex were associated with high ATP. Conclusion There was a strong and statistically significant relationship between income and WTP and ATP for urgent dental care, indicating that access to publicly provided services improved equity for persons with low income.